The successful establishment of a clinical trials unit in the Faculty of Medicine, Chiang Mai University - Kanjanaratanakorn, Kittika; Sukontason, Kom (Biomedical Sciences and Clinical Medicine, 2018)
An evaluation of the utilization and effictiveness of the Clinical Trial Unit (CTU), Chiang Mai University, from the time of its establishment in 2008 to the end of 2015. The evaluation was carried out using key performance indicators including: 1) The number of research project that utilized the CTU; 2) The yearly proportion of income and expenditure of the CTU; 3) The proportion of research projects that utilized the CTU and research projects that involved assessment in research ethics; 4) The meeting of evaluation criteria for being chosen as a research unit by the Contract Research Organization (CRO); 5) Feedback and satisfaction of clients of the CTU. The KPI’s have shown that the number of research project utilizing the CTU increased every year, the largest increase being shown in the year 2014 to 2015 which saw the positive impact of the faculty’s regulation for externally funded research (issue 24 June 2015). Investigation into the financial aspect of the CTU has shown income to be higher than expenditure for the majority of the observed years. In years in which expenditure exceeded income the differential appear to be due to the costs involved in improving the capability of the CTU. The CTU has been selected by both Quintiles, the largest pharmaceutical outsourcing services company in the U.S. and the AO Foundation, a not-for-profit research organization, to be the main research facility in Southeast Asia in order to support multi -center and multi-site research projects. This selection by global organizations is a positive reflection of the unit’s capability and standard. The proportion of research projects involving research ethics that utilized the CTU shows an increasing trend, but remained at 70% in 2014-2015, The evaluation by clients and volunteers in research projects using the Net Promoter score has shown that there is a high level of customer loyalty and satisfaction (rang 40.57 to 71.10). In order to further strengthen the position of the CTU as a leading organization, these improvement strategies should be implemented: 1) Future-proof the infrastructure of the CTU; 2) Bring all aspects of the sample analysis service to international standard; 3) Provide an improved support system for researchers; 4) Future-proof the supply of personnel.